2020
DOI: 10.1007/s11618-020-00955-9
|View full text |Cite
|
Sign up to set email alerts
|

Herkunftsbedingte Leistungsdisparitäten: Die Rolle von Selbstwirksamkeitsüberzeugungen und Unterstützungshandlungen von Eltern und Leistungserwartungen von Lehrpersonen

Abstract: Zusammenfassung Bei der Erklärung von herkunftsbedingten Leistungsdisparitäten spielen neben strukturellen Merkmalen familiäre und schulische Prozessmerkmale eine wichtige Rolle. Die vorliegende Studie versucht, den Zusammenhang zwischen dem elterlichen Ausbildungsniveau und Leistungen in Deutsch und Mathematik mittels Selbstwirksamkeitsüberzeugungen zur Lernunterstützung und Unterstützungshandlungen von Eltern sowie mittels Leistungserwartungen von Lehrpersonen zu erklären. Die Ergebnisse von Strukturgleichun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 66 publications
1
1
0
Order By: Relevance
“…The findings show that parent beliefs, such as information, trust in parent-teacher cooperation, and self-efficacy expectations to support their child, have subject-specific effects on student achievement. In line with previous research, parent self-efficacy expectations influence achievement in German but not in mathematics (Neuenschwander et al, 2005;Niederbacher & Neuenschwander, 2020). Prior research showed stronger effects of parental beliefs on achievement in school language than in mathematics (Epstein, 1991;Neuenschwander et al, 2005).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The findings show that parent beliefs, such as information, trust in parent-teacher cooperation, and self-efficacy expectations to support their child, have subject-specific effects on student achievement. In line with previous research, parent self-efficacy expectations influence achievement in German but not in mathematics (Neuenschwander et al, 2005;Niederbacher & Neuenschwander, 2020). Prior research showed stronger effects of parental beliefs on achievement in school language than in mathematics (Epstein, 1991;Neuenschwander et al, 2005).…”
Section: Discussionsupporting
confidence: 85%
“…High self-efficacy expectation in a subject indicates that parents believe that they can effectively instruct and motivate their child's learning and thus affect student achievement in this subject (Neuenschwander, 2020). However, prior research showed effects of parent self-efficacy expectation on student achievement in German but not in mathematics (Niederbacher & Neuenschwander, 2020). According to Eccles and Harold (1993) parent self-efficacy expectation is reduced as the difficulties of the academic tasks increase.…”
Section: Parent-teacher Cooperation and Student Achievementmentioning
confidence: 99%